El clima laboral y su relación con la felicidad organizacional (2021)
Organizational happiness and working environment have rarely been investigated together, however different documents can be found separately in this regard, therefore, in this research work the close relationship between both concepts can be found and how each influences the other, since both seek the well-being and quality of life improvement of workers. The main objective of this work is to determine the importance of organizational happiness and how it can promote an adequate work environment in the Linking Business company, which is a microenterprise that has less than 10 employees and has already had some issues of work environment between workers and executives because of them, making it hard to have happiness at work, for which the following question was posed: How does organizational happiness influence the work environment of the Linking Business company? To answer this question, a qualitative theoretical-conceptual research is carried out based on existing documents from specialized authors, where it is understood that organizational happiness is an ability developed by a company to generate subjective welfare in its workers, and work environment is the perception that workers have regarding the enterprise and the environment that exists in it. Likewise, a quantitative data analysis is carried out base on a survey made to 7 of this company’s workers about organizational happiness; the responses show the different perceptions each worker has on topics such as: achievements recognition, belonging, knowledge of company’s labor benefits, among others, to notice the improvement aspects that the company could take into account to get a suitable work environment and develop organizational happiness.